Solitary CD8-Positive Primary Cutaneous Peripheral T-Cell Lymphoma: A Question of Classification. (September 2021) - Rolim, Inês; BakShi, Arti; West, Elizabeth; Azurdia, Richard; Kempf, Werner; Robson, Alistair
Abstract : Abstract: Acral CD8(+) lymphoma is a provisional entity in the latest edition of the WHO Lymphoma Classification and is associated with a highly specific dot-like pattern of immunohistochemical expression of CD68. We report a case of an ulcerated solitary cutaneous lesion arising on the forehead of an adult man, which had a CD8(+) cytotoxic phenotype and areas of dot-like CD68 positivity, but with a number of features that significantly detracted from the classically described acral CD8(+) lymphoma. The nosological status of the lesion is discussed with respect to a preferred diagnosis of peripheral T-cell lymphoma, not otherwise specified.